Rural-urban transformation in Uganda - Mukwaya, Paul; Bamutaze, Yazidhi; Benson, Todd; Mugarura, Samuel (Pennsylvania State University Press, 2012)
Over the last twenty years, Uganda has experienced sustained economic growth, increasing urbanization and a sizeable transformation of economic output from agriculture to services. However, this shift in the sources of wealth in the economy has not been accompanied by a shift in employment out of agriculture to the other sectors. This reflects an inability of the more modern sectors of the economy to provide adequate employment for the many Ugandans entering the workforce every year. The relative underperformance of agriculture largely explains why very high income inequalities still persist between rural and urban areas. The government of Uganda recognizes these disparities and has consistently prioritized agricultural and rural development in all of its master development plans. It has also provided significant resources for road construction to better link rural Ugandans to urban market centers. However, the ability of government to effectively implement programs to attain its priorities for agriculture and rural development remains quite limited. Without close attention to putting in place effective public service delivery, the additional revenue from the newly discovered oil is unlikely to lead to the progress desired in rural areas by government.